Building envelope integrated green plants for energy saving. Issue 1 (January 2020) - Tan, Hang; Hao, Xiaoli; Long, Pinhan; Xing, Qingwei; Lin, Yaolin; Hu, Jinhua
In China, rapid urbanization brought about the problems of increased building energy consumption and decreased area of green space as well as poor air quality and heat island effect. Building envelope integrated green plants (BIGP), which is also called as vertical greening, is regarded as the potential solution to the energy and environmental issues. This article verifies and analyzes the energy saving potential of BIGP in China's hot summer and cold winter regions through comparative experiments between a vertical greening room and a reference room. The winter time experiment was carried out from December 2017 to January 2018, and the summer time experiment was from July to August 2018. During winter, the heat flux density of the exterior wall is reduced by 3.11 W/m 2 with BIGP, and the hourly power consumption of the reference room is 1.22 times that of the room with BIGP. The energy saving rate of BIGP is approximately 18%. During summer, the heat flux density of the exterior wall of the reference room is 4.15 W/m 2 larger than that of the vertical green room and the hourly power consumption is 1.33 times that of the vertical greening room. The energy saving rate of BIGP is about 25%.